COVID-19 in chronic myeloid leukemia patients in Latin America. Issue 13 (10th November 2021) - Pagnano, Katia B.; Peralta, Evelyn Herrera; Navarro, Juan Ramon; David Salas, Lourdes del Rosario; Delgado, Nancy; Moiraghi, Beatriz; Toreli, Ana Carolina M.; Perobelli, Leila M.; Fechio, Leonardo; Quixada, Acy T. S.; Funke, Vaneuza; Bendit, Israel; et al.
Abstract: This observational, multicenter study aimed to report the clinical evolution of COVID-19 in patients with chronic myeloid leukemia in Latin America. A total of 92 patients presented with COVID-19 between March and December 2020, 26% of whom were severe or critical. The median age at COVID-19 diagnosis was 48 years (22–79 years), 32% were 60 years or older, and 61% were male. Thirty-nine patients presented with at least one comorbidity (42.3%). Eighty-one patients recovered (88%), and 11 (11.9%) died from COVID-19. There was one case of reinfection. Patients with a major molecular response presented superior overall survival compared to patients with no major molecular response (91 vs. 61%, respectively; p  = 0.004). Patients in treatment-free remission and receiving tyrosine kinase inhibitors showed higher survival rates than patients who underwent hematopoietic stem cell transplantation and those who did not receive tyrosine kinase inhibitors (100, 89, 50, and 33%, respectively; p  < 0.001).